UK LEGAL SYSTEM IN HUMAN VALUE OUT BE CARRIED (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The content of this article from consists of hun thus, in the present day value to the praise of the most widespread human, measures aimed at the protection of the rights and freedoms of individuals and citizens, and focuses on research and activities in foreign countries about human value, directly England law system in ko‘sits out.